Developing a general extended UTAUT model for M-payment adoption. (August 2020) - Al-Saedi, Karrar; Al-Emran, Mostafa; Ramayah, T.; Abusham, Eimad
Abstract: To determine the most frequent factors that extended the Unified Theory of Acceptance and Use of Technology (UTAUT) in the context of Mobile payment (M-payment) adoption, a quantitative meta-analysis approach of 25 studies was undertaken. The results indicated that perceived risk, perceived trust, perceived cost, and self-efficacy were the most frequent factors that achieved significant results in the surveyed studies. Accordingly, this study is an attempt to extend the UTAUT model with these factors; proposing a general extended UTAUT model for M-payment adoption. The proposed model is validated using the partial least squares-structural equation modeling (PLS-SEM) approach. The data were collected from a total of 436 M-payment users in Oman. The results indicated that the best predictor of M-payment users' intention to use the M-payment system is performance expectancy, followed by social influence, effort expectancy, perceived trust, perceived cost, and self-efficacy, respectively. Nonetheless, perceived risk was found to have an insignificant negative impact on the behavioral intention to use M-payment systems. The conclusions derived from this study enhance the understanding of the factors determining the adoption of M-payment systems in Oman. Highlights: A quantitative meta-analysis approach of 25 studies was undertaken. The most commonly used external factors of the UTAUT that achieved significant results in the literature were identified. Perceived risk, perceived trust, perceived cost, and self-efficacy were determined to be the most frequent factors. A general extended UTAUT model is developed through the extension of the model with these factors. Performance expectancy was found to be the most influential factor affecting the users' intention to use M-payment systems.